THE INFLUENCE OF BRAND AMBASSADOR USAGE TOWARD BRAND IMAGE OF OPPO - Fachri Mudzakir (Politeknik Negeri Bandung, 2018)
With the development of technology, the need for sophisticated devices enhances the communication process inthe era of globalization and demands changes in the way marketing and communications management is practisedby individual companies, such as brand ambassadors. A company that pays attention to the use of brandambassador in their marketing activity is Oppo. Whereabouts Oppo can compete in the world and penetrate toIndonesia’s market. The purpose of this study is to identify whether there is an influence of brand ambassador'suse on Oppo brand image. Moreover, the secondary aim of this research is to find out which factors are mostinfluential from Brand Ambassador to brand image of Oppo, and the third is to identify consumer perception ofOppo brand image. Variables that use in this research are brand ambassador and brand image. In this case, datacollected by online questionnaires to 384 respondents to users of Oppo. Data analysis was performed usingmultiple regression analysis and ANOVA using SPSS version 22. The result of this study showed that consumerperception of the brand ambassador has a significant effect on brand image of Oppo. With two of the fourindicators: attractiveness and power are not significantly influential.